Emergency Medical Services - Baratashvili, Alex; Kazakhashvili, Nata (Caucasus Journal of Health Sciences and Public Health, 2020)
The ambulance system (EMS – Emergency Medical System) plays a major role in the organization of medical care for the population. The role of the EMS in critical situations, rapid assessment of acute illnesses, and the organization of medical care for victims of disasters, in the event of accidents and disasters is extremely important. Reorganizing and reforming the ambulance system, changing its forms of management, or standardizing its activities requires scientific evidences. Due to the importance of EMS activities, any state has a great political interest in this field, therefore it is important to create an emergency medical network, which plays a major role in the medical care of the population during various events: epidemic, pandemic, accidents, natural disasters, natural disasters, terrorist attacks, etc. During a series of terrorist attacks in the United States on September 11, 2001, the world community was once again convinced of the role EMS in population health.